Addressing the system-on-a-chip interconnect woes through communication-based design - Sgroi, M.; Sheets, M.; Mihal, A.; Keutzer, K.; Malik, S.; Rabaey, J.; Sangiovanni-Vencentelli, A. (Design Automation, 2001 Proceedings, 2001)
Communication-based design represents a formal method approach to of system-on-a-chip design that considers communication between components as important as the computations they perform. "Our network-on-chip&rdqo ; approach partitions the communication into layers to maximize reuse and provide a programmer with an abstraction of the underlying communication framework. This layered approach is cast in the structure advocated by the OSI Reference network model and is demonstrated with a reconfigurable DSP example. The Metropolis methodology of deriving layers through a sequence of successive adaptation steps between incompatible behaviors refinement of communication is illustrated through the Intercom a design example. In another approach, MESCAL provides a designer with tools for a correct-by-construction protocol stack.